Dynamic thermal and hygrometric simulation of historical buildings: Critical factors and possible solutions. (February 2020) - Akkurt, G.G.; Aste, N.; Borderon, J.; Buda, A.; Calzolari, M.; Chung, D.; Costanzo, V.; Del Pero, C.; Evola, G.; Huerto-Cardenas, H.E.; Leonforte, F.; Lo Faro, A.; et al.
Abstract: Building dynamic simulation tools, traditionally used to study the hygrothermal performance of new buildings during the preliminary design steps, have been recently adopted also in historical buildings, as a tool to investigate possible strategies for their conservation and the suitability of energy retrofit scenarios, according to the boundary conditions. However, designers often face with the lack of reliable thermophysical input data for various envelope components as well as with some intrinsic limitations in the simulation models, especially to describe the geometric features and peculiarities of the heritage buildings. This paper attempts to bridge this knowledge gap, providing critical factors and possible solutions to support hygrothermal simulations of historical buildings. The information collected in the present work could be used by researchers, specialists and policy-makers involved in the conservation of building's heritage, who need to address a detailed study of the hygrothermal performance of historical buildings thorugh dynamic simulation tools. Highlights: The discrepancy between actual performance and simulations is too large. Several factors affect the reliability of energy simulation of historical buildings. Possible solutions and guidelines for practitioners have been provided.